Hydroxytyrosol Ameliorates Colon Inflammation: Mechanistic Insights into Anti-Inflammatory Effects, Inhibition of the TLR4/NF-κB Signaling Pathway, Gut Microbiota Modulation, and Liver Protection - Jiali Tang; Mengyao Zhang; Jiaying Wang; Haijing Zhang; Zhong Wang; Ziteng Lei; Chengtao Wang; Wei Chen (Foods)
Inflammatory bowel disease (IBD) is a chronic disease influenced by a complex interplay of factors, including genetics, environmental, and gut microbiota. This study aimed to explore the therapeutic potential of the natural polyphenolic compound hydroxytyrosol (HT) in modulating dextran sodium sulfate (DSS)-induced colitis in mice. The findings demonstrate that oral administration of HT significantly alleviated colitis symptoms, as evidenced by a reduction in the disease activity index and improvements in colonic pathology. HT was found to inhibit the release of pro-inflammatory cytokines, enhance antioxidant status, and mitigate oxidative stress. Furthermore, HT contributed to the restoration of the gut barrier by reinstating tight junction proteins, reducing the inflammatory marker lipopolysaccharide (LPS), and suppressing inflammation-related genes. This compound also modulated the NLRP3-Cas-1-GSDMD-IL-1β inflammatory pathway and inhibited the NF-κB (nuclear factor kappa B) pathway, thereby alleviating colitis. Gut microbial analysis revealed that HT enriched the abundance of Bacteroidota and altered the balance between Bacteroidota and Firmicutes in mice. Correlation analysis between bacterial microbiota and inflammatory factors suggested that HT may alleviate colitis by modulating the relative abundance of Alistipes, Bacteroides, and unclassified_f__Muribaculaceae. These findings underscore the potential of HT as a therapeutic agent in the treatment of colitis.